La política archivística del Gobierno español y la ausencia de gestión del pasado desde el comienzo de la transición - González Quintana, Antonio (Hispania Nova. Revista de Historia Contemporánea, 2007)
Most of political parties represented at the Spanish Parliament agreed, after Franco’s death, not to face the recent past. From the beginning of the Spanish political transition has existed neither a policy of memory nor a real archival policy regarding that subject. The management of the records produced by D.N.S.D. (National Delegation of Documentary Services, the information agency of Franco regime in Salamanca), was only focused on improving historical researches. The archives of military courts, used for massive civilian repression in ther forties, thirty years after continue being the biggest gap in Spanish archival legislation. No measures have been adopted to provide accountability about Human Rights violations or to facilitate the spreading of compensations for victims of repression.

Archivos y Derechos Humanos en Argentina - Karababikian, Graciela (Bolétin del Archivo General de la Nación, 2007)

Los archivos de los derechos humanos en el Perú - Ruth Elena Borja Santa Cruz (Historizar el pasado vivo en América Latina, 2007)
Keywords: References - Boel et al. (2021), Archives and Human Rights

Pasado y presente de la violencia en Colombia | Daniel Ricardo Peñaranda Supelano | Universilibros - Sánchez, Gonzalo; Peñaranda, Ricardo (La Carreta Editores E.U., 2007)
📚 Durante los últimos veinte años Pasado y presente se convirtió en un referente de los estudios sobre La Violencia. Cuando aún no se hablaba entre
Keywords: References - Boel et al. (2021), Archives and Human Rights

La política archivística del Gobierno español y la ausencia de gestión del pasado desde el comienzo de la transición - Quintana, Antonio González (Hispania nova, Revista de Historia Contemporánea, 2007)
Most of political parties represented at the Spanish Parliament agreed, after Franco’s death, not to face the recent past. From the beginning of the Spanish political transition has existed neither a policy of memory nor a real archival policy regarding that subject. The management of the records produced by D.N.S.D. (National Delegation of Documentary Services, the information agency of Franco regime in Salamanca), was only focused on improving historical researches. The archives of military courts, used for massive civilian repression in ther forties, thirty years after continue being the biggest gap in Spanish archival legislation. No measures have been adopted to provide accountability about Human Rights violations or to facilitate the spreading of compensations for victims of repression.
Keywords: References - Boel et al. (2021), Archives and Human Rights